2015
DOI: 10.1002/mc.22266
|View full text |Cite
|
Sign up to set email alerts
|

A biphasic response pattern of lipid metabolomics in the stage progression of hepatitis B virus X tumorigenesis

Abstract: Metabolic syndrome has closely linked to the development of human hepatocellular carcinoma (HCC). By using the hepatitis B virus (HBV) X (HBx) transgenic mouse model, we studied the dynamic evolution of serum and liver profiles of lipids and global cDNA expression at different stages of HBx tumorigenesis. We observed that the lipid (triglycerides, cholesterol, and fatty acids) profiles revealed a biphasic response pattern during the progression of HBx tumorigenesis: a small peak at early phase and a large peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…Several studies have already reported differences in the species of TG in tumor tissues . The major species of SFA and MUFA, palmitic acid (C16:0) and oleic acid (C18:1), were higher in the tumor region, and PUFA, including linoleic acid (C18:2), was lower in the tumor region than in the nontumor region, which was consistent with our results.…”
Section: Resultssupporting
confidence: 92%
“…Several studies have already reported differences in the species of TG in tumor tissues . The major species of SFA and MUFA, palmitic acid (C16:0) and oleic acid (C18:1), were higher in the tumor region, and PUFA, including linoleic acid (C18:2), was lower in the tumor region than in the nontumor region, which was consistent with our results.…”
Section: Resultssupporting
confidence: 92%
“…Analysis of lipid metabolites in HBx transgenic mice showed that arachidonate 5-lipoxygenase, lipoprotein lipase, fatty acid binding protein 4, 1-acylglycerol-3-phosphate O-acyltransferase 9, and apolipoprotein A-IV expression are all induced [353]. Furthermore, HBx-transgenic mice exhibit elevated levels of cholesterol and triglycerides, as well as activated expression of the key transcription factors in lipid homeostasis [353], such as the prolipogenic sterol regulatory element binding protein 1 (SREBP-1), liver X receptor [354], C/EBP1 and peroxisome proliferator-activated receptor γ (PPARγ) [355].…”
Section: Hepatitis C Virusmentioning
confidence: 99%
“…Furthermore, HBx-transgenic mice exhibit elevated levels of cholesterol and triglycerides, as well as activated expression of the key transcription factors in lipid homeostasis [353], such as the prolipogenic sterol regulatory element binding protein 1 (SREBP-1), liver X receptor [354], C/EBP1 and peroxisome proliferator-activated receptor γ (PPARγ) [355]. In turn, liver PPAR-γ and SREBP-1c up-regulation in parallel with PPAR-α down-regulation enhance de novo lipogenesis and reduce fatty acid oxidation [356].…”
Section: Hepatitis C Virusmentioning
confidence: 99%
“…Recently, the ground glass hepatocytes, which harbor two HBV oncoproteins, the pre-S mutant surface antigen and the hepatitis B X protein (HBx), have been proposed as the precursor lesions of HCC (Wu et al, 2014;Yen et al, 2016). HBx is an etiologic factor of HBV-related hepatocarcinogenesis through its multiple functions in regulation of cell cycle, cell proliferation, lipid metabolism, signal transduction, and gene transcription (Arbuthnot et al, 2000;Chisari et al, 1989;Teng et al, 2016). Overexpression of HBx can cause tumorigenicity in an HBx transgenic mouse model (Newell et al, 2008).…”
Section: Introductionmentioning
confidence: 99%